Aspects of Avatime phonology - Russell G. Schuh (LibraryPress@UF, 1995)
Avatime is one of 14 Central-Togo languages (formerly known as "Togo Remnant Languages") spoken in the Volta Region of Ghana and contiguous areas of Togo. The most striking typological feature of these languages compared to their closest Kwa relatives is the fact that they have active noun class systems. The present paper is a description of Avatime phonology, with emphasis on certain features which have been poorly described and/or are of general linguistic interest. Within the consonant system, Avatime has bilabial fricatives and a full series of labiovelar obstruents, including fricatives. Consonants with following glides are considered to be segment sequences rather than consonants with secondary articulations. The vowel system has nine vowels with [ATR] harmony. Continguous vowels undergo a variety of coalescence processes, which differ depending on morphological context and the specific vowels involved. Modem Avatime requires an analysis with four contrasting level tones. However, many instances of two of these tones (the highest level and the lower mid level) are derived through still active processes. One feature of the tone system not previously described is the presence of glottal stop following a syllable bearing non-low tone when that syllable falls at a phonological phrase boundary.